Global change in marine aquaculture production potential under climate change. Issue 11 (November 2018) - Froehlich, Halley; Gentry, Rebecca; Halpern, Benjamin
Abstract Climate change is an immediate and future threat to food security globally. The consequences for fisheries and agriculture production potential are well studied, yet the possible outcomes for aquaculture (that is, aquatic farming)—one of the fastest growing food sectors on the planet—remain a major gap in scientific understanding. With over one-third of aquaculture produced in marine waters and this proportion increasing, it is critical to anticipate new opportunities and challenges in marine production under climate change. Here, we model and map the effect of warming ocean conditions (Representative Concentration Pathway scenario 8.5) on marine aquaculture production potential over the next century, based on thermal tolerance and growth data of 180 cultured finfish and bivalve species. We find heterogeneous patterns of gains and losses, but an overall greater probability of declines worldwide. Accounting for multiple drivers of species growth, including shifts in temperature, chlorophyll and ocean acidification, reveals potentially greater declines in bivalve aquaculture compared with finfish production. This study addresses a missing component in food security research and sustainable development planning by identifying regions that will face potentially greater climate change challenges and resilience with regards to marine aquaculture in the coming decades. Understanding the scale and magnitude of future increases and reductions in aquaculture potential is critical for designing effective and efficient use and protection of the oceans, and ultimately for feeding the planet sustainably. Marine aquaculture is a rapidly growing global source of food, but is likely to be affected by climate change. Here, the effect of warming oceans on the production potential of 180 cultured finfish and bivalve species is mapped over the next century.